Build Strategies Based on Substrate Utilization for 3-Axis Hybrid Wire Arc Additive Manufacturing Process - Ritam Sarma; Sajan Kapil; Shrikrishna N. Joshi (Advances in Materials Science and Engineering)
The hybrid wire arc additive manufacturing (H-WAAM) process is one of the prominent methods for realizing large near-net-shaped metallic objects. In this process, a CAD model of the component is sliced into a set of 2D contours followed by the generation of toolpaths. An arc welding torch then follows these toolpaths for adding material over a substrate to realize the near-net shape of the object. These near-net-shaped objects are then followed by a machining operation to convert them into a fully functional part. It is always anticipated that the near-net shape of an object is produced quickly and upholds a high geometrical accuracy. Conventionally, the deposition rate is increased to reduce the build time but with a compromisation in the geometrical accuracy and material integrity. Therefore, in this work, the authors have investigated three substrate utilization methods, viz., (i) reusable substrate, (ii) embedded substrate, and (iii) integrated substrate to achieve the same goal. The build strategies for these three substrate utilization methods are illustrated through several examples. Also, a case study was performed for fabricating an impeller-like structure through a 3-axis H-WAAM setup. It has been observed that the embedded substrate method exhibits superior geometrical accuracy and takes less time to build the part as compared to other methods. A maximum of 64.34% of the material and 89.17% of build time is saved by adopting proposed build strategies compared with the traditional subtractive process.